TO COMPARE THE SEALING ABILITY OF TWO DIFFERENT SEALERS AFTER USING CHLORHEXIDINE AS FINAL IRRIGANT-An invitro study - SARANYA DHANAPAL; NIVEDHITHA MALLI SURESHBABU (International Journal of Pharma and Bio Sciences, 2016)
The aim of this study was to compare the sealing ability of two different sealers after using chlorhexidine as a final irrigant. Twenty single rooted teeth were randomly divided into two groups according to different obturation materials (the AH Plus, Gutta-percha group and Acroseal, Gutta percha group). The groups were further divided into two subgroups containing five teeth each according to the irrigation regimen, and they were subjected to a universal testing machine for evaluating pushout bond strength. Post hoc pair-wise comparisons were performed using Tukey multiple comparisons for statistical analysis using SPSS 15 Software. The mean value of the AH Plus Gutta-percha group, without precipitate formation revealed the highest mean value for the bond strength, which was statistically higher (P <0.001) than the remaining groups. Formation of precipitate by combination of sodium hypochlorite and chlorhexidine tends to affect the bond strength of root canal sealers when used for obturation.